Pendekatan Materialist untuk Studi Komunikasi Indonesia - Holy Rafika Dhona (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2023)
ABSTRACT This paper advocates for a materialist approach to studying communication in Indonesia. This paper questions the communication/media study approach in Indonesia, which only has two approaches when looking at the ontological reality of communication: message transmission or meaning production. This paper explains that these two approaches are not absolute truths. Both of these approaches are historical products and have contributed to the stagnation of communication studies, so an alternative approach, such as a materialist approach, is needed in communication studies. This paper then describes some of the initial ideas of the materialist approach which defines communication as the circulation of people, ideas, information and capital. Furthermore, this paper also shows the development of this approach in several regions such as Europe and North America, where communication studies are understood as studies of material realities that are neglected as objects of communication studies by the message transmission process approach and the meaning production approach. This paper then outlines several alternative syntheses for developing approaches in communication studies in Indonesia, including alternative fields proposed by North American scholars namely; political economy, technological infrastructure, space, body and discourse. As a recommendation, this paper calls on Indonesian communication scholars to discuss and practice a materialist approach so that their studies will not only be limited to issues of media content, meaning, or media-centric things.ABSTRAKTulisan ini adalah upaya mengadvokasi pendekatan materialist dalam studi komunikasi di Indonesia. Untuk mengusulkan pendekatan ini, tulisan ini mempersoalkan pendekatan studi komunikasi/media di Indonesia yang hanya memiliki dua pendekatan ketika melihat realitas ontologis komunikasi; sebagai proses transmisi pesan atau sebagai proses produksi makna. Tulisan ini menjelaskan bahwa dua pendekatan ini bukan kebenaran absolut. Kedua pendekatan tersebut merupakan produk sejarah dan turut menjadi penyebab studi komunikasi berada dalam stagnansi, sehingga dibutuhkan pendekatan alternatif dalam studi komunikasi seperti pendekatan materialist. Tulisan ini kemudian menjelaskan beberapa gagasan awal pendekatan materialist yang mendefinisikan komunikasi sebagai sirkulasi orang, ide, informasi dan modal/kapital. Lebih jauh, tulisan ini juga menjelaskan perkembangan pendekatan ini di beberapa wilayah seperti Eropa dan Amerika Utara, dimana studi komunikasi dipahami sebagai studi atas realitas material yang tidak dianggap sebagai objek studi komunikasi oleh pendekatan proses transmisi pesan dan pendekatan produksi pemaknaan yang berfokus pada realitas simbolik/virtual. Tulisan ini kemudian menguraikan beberapa sintesis alternatif untuk perkembangan pendekatan dalam studi komunikasi di Indonesia termasuk di antaranya alternatif bidang yang diusulkan oleh para sarjana Amerika Utara yakni; ekonomi politik, infrastruktur teknologi, ruang, tubuh dan wacana. Sebagai rekomendasi, tulisan ini memanggil para sarjana komunikasi Indonesia untuk mendiskusikan dan mempraktikkan pendekatan materialist sehingga studi mereka tidak hanya akan terbatasi pada masalah pesan, makna atau pembahasan yang terfokus pada media.